Community‐Driven Hypothesis Testing: A Solution for the Tragedy of the Anticommons. Issue 3 (11th July 2017) - Palma‐Oliveira, José Manuel; Trump, Benjamin D.; Wood, Matthew D.; Linkov, Igor
Abstract: Shared ownership of property and resources is a longstanding challenge throughout history that has been amplifying with the increasing development of industrial and postindustrial societies. Where governments, project planners, and commercial developers seek to develop new infrastructure, industrial projects, and various other land‐and resource‐intensive tasks, veto power shared by various local stakeholders can complicate or halt progress. Risk communication has been used as an attempt to address stakeholder concerns in these contexts, but has demonstrated shortcomings. These coordination failures between project planners and stakeholders can be described as a specific kind of social dilemma that we describe as the "tragedy of the anticommons." To overcome such dilemmas, we demonstrate how a two‐step process can directly address public mistrust of project planners and public perceptions of limited decision‐making authority. This approach is examined via two separate empirical field experiments in Portugal and Tunisia, where public resistance and anticommons problems threatened to derail emerging industrial projects. In both applications, an intervention is undertaken to address initial public resistance to such projects, where specific public stakeholders and project sponsors collectively engaged in a hypothesis‐testing process to identify and assess human and environmental health risks associated with proposed industrial facilities. These field experiments indicate that a rigorous attempt to address public mistrust and perceptions of power imbalances and change the pay‐off structure of the given dilemma may help overcome such anticommons problems in specific cases, and may potentially generate enthusiasm and support for such projects by local publics moving forward.